The Islamic Models Of Corporate Governance - Jamaludin, Azahari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Corporate governance is one of the crucial elements of any corporation development as it plays roles to strategize and promote principles of accountability, fairness and transparency. Nevertheless, it is observed that there is not much discussion or literature on the issue of corporate governance from the Islamic standpont. It is strongly indicated that any Islamic corporation needs to have a strong governance model and proper strategies that will stimulate the adoption of solid and operative corporate governance within the Islamic paradigm. Current study is envisioned to offer an overview on the concept, principles and model of corporate governance from Islamic standpoint focuses on the governance framework of Islamic institutions.